Innovation in Sukuk market: the case of Abu Dhabi perpetual Sukuk - Hasan, Aznan; Abu Samah, Zariah; Mohamed, Siti Hasmah; Zein Isma, Syaza Nawwarah (2013)
The continuing innovations in Islamic finance has positively elevated the Islamic finance industry,especially for Sukuk or Islamic securities. Sukuk market is experiencing the most significant growth in relation to the other components of Islamic finance. There are numerous innovations in developing Sukuk structure, which has made it a popular financial instrument for raising capital/funding requirement via issuance of corporate Sukuk attached with attractive features and benefits for investors. In 2012, Abu Dhabi Investment Bank (ADIB) had successfully issued the world’s first Tier 1 perpetual Sukuk. The huge success recorded had lead to other similar perpetual Sukuk structure issued by Dubai Islamic Bank in 2013. The simplicity of the Sukuk structure coupled with transparent and favourable features attached to ADIB Sukuk are among the successful contributing factors.This paper will analyses and discuss the structure, salient features and operational mechanism of its “perpetual characteristic”. Being the first of its kind, this paper will also shades some light on potential Shariah issues for deliberation and consideration for future structuring of perpetual Sukuk